(3TQM GdcGajIs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3YHO GdbGOQ Hf EHQGgje Hf Ydi GdfhGd s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg U heG jbHdg GdecGf GdGeHgGT jYfi Gf GSe GdecGf dGjbHd GdXQajI efgG EdG Gdeje s
(3BNQgG (B:s
(3U aCMeO Gddg eUdjkG Ydi eMeO NjQ fHi CQSdG hGdg GdZQ GdcQGe T deG Cced eQGOg NJe cJGHg HGdUdGI Ydi SjOfG eMeO Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdfMhs